2004
DOI: 10.1136/bjsm.2003.009399
|View full text |Cite
|
Sign up to set email alerts
|

Improving golf performance with a warm up conditioning programme

Abstract: Objectives: To determine whether a golf specific warm up programme (both immediately prior to play and after performing it five times a week for 5 weeks) improved performance in 10 male golfers compared with 10 controls matched for age, sex, and handicap. Methods: Twenty male golfers were matched for age (¡2 years) and handicap (¡1 stroke). Club head speed was assessed by two dimensional video analysis in a laboratory setting. In week 1, all golfers performed 10 strokes. In weeks 2 and 7, the controls underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 19 publications
1
42
1
2
Order By: Relevance
“…Each subject performed a standardized 10 min warm-up based on Fradkin et al (2004). Subjects then familiarized themselves with the laboratory environment by hitting balls into a net.…”
Section: Methodsmentioning
confidence: 99%
“…Each subject performed a standardized 10 min warm-up based on Fradkin et al (2004). Subjects then familiarized themselves with the laboratory environment by hitting balls into a net.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that different warm-up exercises may have different effects on club head speed, distance, accuracy, and consistent ball contact. 10,16 It is a limitation of this study that every golfer performed self-selected warm-up exercise that might have affected the results of this study. A standardized warm-up would be a better choice for future studies.…”
Section: Key Pointsmentioning
confidence: 98%
“…Each participant was asked to warm up with large dynamic movements and static stretches prior to testing (Fradkin, Sherman, & Finch, 2004). All participants used their own private driver clubs for the golf swing and were allowed to adapt to the indoor environment used in the study with practice.…”
Section: Experimental Set-up and Data Collectionmentioning
confidence: 99%